Massive haemorrhage due to ulcerative colitis presenting as melaena. Issue 803 (September 1992) - Aristodemou, A.; Ryder, S.; Jacyna, M. R.
Abstract : We present a patient with known ulcerative colitis who presented with massive lower gastrointestinal bleeding in the form of melaena. Extensive investigations indicated that the source of blood loss was only from the colon, was attributable to the colitis, and settled when the colitis was treated with steroids. Melaena may be due to blood loss from the colon.